Appraisal of the impact of knotty tissues on the wood properties utilization: A Systematic review (Agriculture, Food, and Natural Resources Journal, 2026)
This study comprehensively reviews the influence of knots on the physical, mechanical, and chemical properties of wood, with particular emphasis on their implications for material performance utilization. Knots are anatomically distinct from surrounding wood tissue, being denser, harder, more resinous, and exhibiting different shrinkage behavior. Several experimental results indicate that wood density increases with increasing knot area in the cross section, while volumetric shrinkage decreases. In contrast, mechanical properties such as bending strength, modulus of elasticity (MOE), and impact bending strength show a pronounced reduction as knot area increases. Specimens containing a high proportion of knots also exhibit lower compression strength parallel to the grain compared with clear wood. Hardness values are significantly higher within knotted regions, whereas adjacent knot-free areas display reduced hardness. Beyond mechanical performance, knots adversely affect appearance quality, machining behavior, adhesive performance, and chemical uniformity, thereby reducing the overall use value and economic value of wood products. Although the higher density of knots has limited influence on the bulk density of wood, suggesting that knotty clear wood may be treated similarly in density-based applications, the presence of knots significantly alters other critical properties that govern structural performance and processing efficiency. These findings provide a systematic understanding of the role of knots in wood quality and serve as a baseline for material selection, grading, and utilization strategies in wood-based industries.
Keywords: Knot; Machining performance; Mechanical properties; Physical properties; Wood quality